Civic and Uncivic Values in Slovakia
XXIV, 344 p. 22 illus.
Keywords: “The essays gathered in this collection offer a nuanced and insightful exploration of how values—civic, national, liberal, and illiberal—are shaped, contested, and deployed in contemporary Slovak society. The volume combines impressive breadth—from analyses of populist rhetoric to examinations of feminism, Roma exclusion, and civic culture—with scholarly rigour and deep familiarity with the subject. Collectively, these contributions provide a timely and richly contextualized understanding of Slovakia's evolving democratic landscape.” —James Krapfl, McGill University, Canada Like other countries in East Central Europe, the Slovak Republic is facing new challenges which were not on the horizon at the time the communist system collapsed and there are worries that this country, with the pro-Russian Prime Minister Robert Fico now at the helm, might be at risk of democratic backsliding. One of the key factors determining whether Slovakia will weather its current political difficulties or slide away from democracy is the strength of civic values such as tolerance, respect for the equality of people, and readiness to play by the rules of the political game. This book looks at the record of the Slovak Republic in the years since 1993, taking into consideration politics, values as reflected in public opinion surveys, gender inequality, and the values communicated in literature, religion, and film. In addition, the volume takes a look at ethnic minorities, focusing especially on Slovakia’s Hungarian minority. Sabrina P. Ramet is a Professor Emerita in the Department of Sociology & Political Science at the Norwegian University of Science & Technology (NTNU), Norway. Vladimir Ðorđević is an Associate Professor in the Department of Security Studies, Faculty of Security Management, Police Academy of the Czech Republic, Prague, Czech Republic. Christine Marie Hassenstab is a retired attorney who has also worked as an Adviser in the EU Grants Office at the Norwegian University of Science & Technology (NTNU), in Trondheim, Norway. She earned her Ph.D. in Sociology at NTNU in 2010.